(3TQM WhGdY GdCfhGQs - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO CHh GdNjQ fGUQ GdOjf GdHjVGhj,J (B685 (3g` s
(3ChdgG (B:s
(3Yde hGMO jJYdb Hcd TF ef GdcdjGJ hGdLReGJ GdeMSheGJ hGdeYbhdGJ s
(3BNQgG (B:s
(3HQMeJc jG CQMe GdQGMejf s
(3GdfSNI HgG MhGTs
(3WhGdY GdCfhGQ GdHjVGhi GfXQ cTa GdXfhf L (B2 (3U`(B1116s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJhMjO hGdedd hGdfMds